The Impact of Poverty, Human Development, and Zakat Contributions on Economic Growth in Indonesia and Malaysia - Naurah Bayu, Luthfiyyah; Anwar Fathoni, Muhammad (KnE Social Sciences, 2024)
The paradigm of the conventional economic theory states that economic growth affects poverty levels and human development, but this study proves the opposite. The economic growth influences the poverty level and human development. This study investigates the impact of poverty, human development, and the zakat fund on economic gowth in Indonesia and Malaysia between 2011 and 2020. Indonesia and Malaysia are two countries that have close characteristics, namely countries with a Muslim majority in Southeast Asia that develop zakat. The quantitative method will be used in this study using secondary data. The analytical technique used in this research is panel data regression analysis. This study demonstrates that poverty, human development, and zakat funds affected the economic growth in Indonesia and Malaysia from 2011 to 2020. Keywords: economic growth, poverty, zakat, religious charity, index of human development